A Murine Model of Mild Traumatic Brain Injury Exhibiting Cognitive and Motor Deficits - Yang, Sung H. (2013)
BACKGROUND: Mild traumatic brain injury is a serious public health concern, affecting more than 1.7 million people in the United States annually. Mild TBI is difficult to diagnose and is clinically associated with impaired motor coordination and cognition. METHODS: Mice were subjected to a mild TBI (mTBI-1 or mTBI-2) induced by a weight drop model. Brain injury was assessed histologically and biochemically, the latter by serum neuron specific enolase (NSE) and glial fibrillary acidic protein (GFAP). Systemic and brain inflammation were measured by cytokine array. Blood brain barrier (BBB) integrity was determined by cerebral vascular leakage of micromolecular and macromolecular fluorescent molecules. Mice were evaluated using a rotarod device and novel object recognition to measure motor coordination and cognition, respectively. RESULTS: Mice undergoing mTBI-1 or mTBI-2 had significant deficits in motor coordination and cognition for several days after injury compared to controls. Furthermore, we found both mTBI-1 and mTBI-2 caused micromolecular leakage in the BBB, whereas only mTBI-2 caused macromolecular leakage. Serum NSE and GFAP were elevated acutely and corresponded to the degree of injury, but returned to baseline within 24 hours. Serum cytokines interleukin-6 (IL-6) and keratinocyte-derived chemokine (KC) were significantly increased within 90 minutes of TBI. IL-6 levels correlated with the degree of injury. CONCLUSION: The current study provides a reproducible model of mild TBI in mice that exhibits pathological features of mild TBI in humans. Furthermore, our data suggest that serum cytokines, such as IL-6, may be effective biomarkers for severity of head injury.